The impact of occupational shift work and working hours during pregnancy on health outcomes: a systematic review and meta-analysis - Cai, Chenxi; Vandermeer, Ben; Khurana, Rshmi; Nerenberg, Kara; Featherstone, Robin; Sebastianski, Meghan; Davenport, Margie H. (American journal of obstetrics and gynecology, 2019)
An increasing number of original studies suggest that exposure to shift work and long working hours during pregnancy could be associated with the risk of adverse pregnancy outcomes, but the results remain conflicting and inconclusive. To examine the influences of shift work and longer working hours during pregnancy on maternal and fetal health outcomes. Five electronic databases and 3 gray literature sources were searched up to March 15, 2019. Studies of all designs (except case studies and reviews) were included, which contained information on the relevant population (women who engaged in paid work during pregnancy); exposure (rotating shift work [shifts change according to a set schedule], fixed night shift [typical working period is between 11:00 pm and 11:00 am] or longer working hours [>40 hours per week]);comparator (fixed day shift [typical working period is between 8:00 am and 6:00 pm] or standard working hours [≤40 hours per week]); and outcomes (preterm delivery, low birthweight [birthweight <2500 g], small for gestational age, miscarriage, gestational hypertension, preeclampsia, intrauterine growth restriction, stillbirth, and gestational diabetes mellitus). From 3305 unique citations, 62 observational studies (196,989 women) were included. “Low” to “very low” certainty evidence from these studies revealed that working rotating shifts was associated with an increased odds of preterm delivery (odds ratio, 1.13; 95% confidence interval, 1.00–1.28, I2 = 31%), an infant small for gestational age (odds ratio, 1.18, 95% confidence interval, 1.01–1.38, I2 = 0%), preeclampsia (odds ratio, 1.75, 95% confidence interval, 1.01–3.01, I2 = 75%), and gestational hypertension (odds ratio, 1.19, 95% confidence interval, 1.10–1.29, I2 = 0%), compared to those who worked a fixed day shift. Working fixed night shifts was associated with an increased odds of preterm delivery (odds ratio, 1.21; 95% confidence interval, 1.03–1.42; I2 = 36%) and miscarriage (odds ratio, 1.23; 95% confidence interval, 1.03–1.47; I2 = 37%). Compared with standard hours, working longer hours was associated with an increased odds of miscarriage (odds ratio, 1.38; 95% confidence interval, 1.08–1.77; I2 = 73%), preterm delivery (odds ratio, 1.21; 95% confidence interval, 1.11–1.33; I2 = 30%), an infant of low birthweight (odds ratio, 1.43; 95% confidence interval, 1.11–1.84; I2 = 0%), or an infant small for gestational age (odds ratio, 1.16, 95% confidence interval, 1.00–1.36, I2 = 57%). Dose–response analysis showed that women working more than 55.5 hours (vs 40 hours) per week had a 10% increase in the odds of having a preterm delivery. Pregnant women who work rotating shifts, fixed night shifts, or longer hours have an increased risk of adverse pregnancy outcomes.